Application of cloud technologies in the study of higher mathematics - T. I. Zhylenko; N. M. Zakharchenko (Academy of Cognitive and Natural Sciences, 2013)
Under the conditions of Ukraine's transition from an industrial society to an information society and the globalization of the Ukrainian educational space, issues related to the development of cloud technologies in education become relevant. Reformatting the educational link is the restructuring of the learning process. A few years ago, to find out the schedule of classes, you had to go to the university, look for it on the bulletin board and write it in the diary. Today, such a need has disappeared, it can be done from the comfort of home. Using the Internet, you can also consult with a teacher, send him questions; work on a lecture, a practical lesson, for example in higher mathematics: find software packages for the construction of second-order surfaces, choose the best of them and apply them to calculate the volume of the body, finding the circulation or flow of a vector field, etc.